ADDENDA (Journal of Semitic studies, 1977)
1. To p-35, last paragraph: This book has been published in the meantime with the subtitle A Samaritan Sect in Late Antiquity.2. To p. 41, n.5: Cf. also R. Pummer, “The Samaritan Pentateuch and the New Testament”, N.T.S. xxin (1975–6),441–3.